Investigation Of The Effects Of Aqueous Extract Of Cissus Pupulnea Stem On Some Selected Reproductive Hormones And Haematology Of Treated Rats - Momoh Shaibu (CV Media Inti Teknologi, 2025)
The study investigated the effects of aqueous extract of Cissus populnea stem on selected reproductive hormones and haematology of treated rats. Ten albino rats, averaging 190 g in weight, were divided into two groups of five. Group A (control) received 50mg/g body weight of commercial feed and distilled water, while Group B received 50mg/g body weight of the extract, commercial feed, and water daily using a plastic syringe. After 30 days of treatment, the rats were sacrificed using a mixture of acetone and chloroform. Blood and testes were collected to observe the extract's effects on hormones and haematology. The testes/body weight ratio showed no significant differences (P > 0.05). However, hormone profile results indicated significant (p < 0.05) increases in luteinizing hormone, follicle-stimulating hormone, testosterone, estrogen, and progesterone, and a significant (P > 0.05) decrease in prolactin in the treated rats. Haematological analysis revealed significant (p < 0.05) increases in red blood cell count, lymphocyte percentage, white blood cell count, packed cell volume, and platelet count, but significant (P > 0.05) decreases in mean corpuscular volume, mean corpuscular haemoglobin, and neutrophil percentage. The study concluded that Cissus populnea extract positively affects reproductive hormones and haematology, boosting the sexual reproductive hormones in the treated rats.